Traveling Waves and Space-Time Chaos in the Kawahara Equation - Magnitskii, Nikolai A. (Journal of Applied Nonlinear Dynamics, 2026)
The work carried out an analytical and numerical analysis of the transition to space-time chaos in the nonlinear Kawahara equation through cascades of bifurcations of traveling waves in accordance with the universal bifurcation scenario of Feigenbaum-Sharkovsky-Magnitskii. It has been proven that the bifurcation parameter in this case is the propagation velocity of traveling waves along the spatial axis, which is clearly not included in the original equation.